Experimental Study on Skin Temperature of People in Office Activities at Different Air Temperatures - R. A., Bakar; Norfadzilah, Jusoh; Ahmad Rasdan, Ismail; Tanti Zanariah, Shamshir Ali; Musthafah, Mohd Tahir (2016)
The present study aims to understand the effect of skin temperature on the preferred air temperature in an office environment. Fifteen subjects chose the preferred air temperature in a climate chamber. There are five air temperature was chose which is 19, 21, 23, 26 and 29 oC and was exposed in the climate chamber. The study found that air temperature ranges between 19 oC - 29 oC and different metabolic rate give a difference skin temperature level that indicates the level of comfort by subjects. Analysis of skin temperature showed that levels of temperatures vary, depending on the BMI considered and the subject.